2016
DOI: 10.1080/15384101.2016.1152425
|View full text |Cite
|
Sign up to set email alerts
|

An integrative analysis of reprogramming in human isogenic system identified a clone selection criterion

Abstract: Kiselev (2016) An integrative analysis of reprogramming in human isogenic system identified a clone selection criterion, Cell Cycle, 15:7, 986-997, DOI: 10.1080/15384101.2016 ABSTRACTThe pluripotency of newly developed human induced pluripotent stem cells (iPSCs) is usually characterized by physiological parameters; i.e., by their ability to maintain the undifferentiated state and to differentiate into derivatives of the 3 germ layers. Nevertheless, a molecular comparison of physiologically normal iPSCs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…should be used for reprogramming remains open. According to our results and other studies, isogenic iPSCs derived from different somatic cell types are functionally similar [5, 7]. However, taking into account the fact that they should be further differentiated into specialized types of cells in vitro , it is necessary to know how their ability to differentiate would vary.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…should be used for reprogramming remains open. According to our results and other studies, isogenic iPSCs derived from different somatic cell types are functionally similar [5, 7]. However, taking into account the fact that they should be further differentiated into specialized types of cells in vitro , it is necessary to know how their ability to differentiate would vary.…”
Section: Introductionsupporting
confidence: 66%
“…We used the cell lines hESM01, hESM01n5 (hereinafter n5), fibroblasts, neurons, retinal pigment epithelial cells differentiated from hESM01n5 (F, N, R, respectively), and the iPSC lines iF, iN, iR obtained by genetic reprogramming of the lines F, N, R, respectively [5]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While initially there were concerns that iPSCs may be different than embryonic stem cells and less suitable for transplantation (Rohani et al, 2014), more recent work has demonstrated that iPSCs and embryonic stem cells are highly analogous if not completely identical (Shutova et al, 2016). Autologous stem cell transplantation is commonly performed with mesenchymal stem cells and numerous strategies have been devised to enhance their therapeutic efficacy.…”
Section: Prospective Therapiesmentioning
confidence: 99%
“…Для более точного отбора линий ИПСК, соответствую-щих ранее существовавшим ЭСК, нами была определена панель из 280 генов, экспрессия которых позволяет мини-мум из 5 независимо отобранных клонов выбрать наиболее «совершенную» линию [33]. Помимо существенного изме-нения транскрипционного паттерна, репрограммирова-ние сопровождается глобальными изменениями на уровне эпигенома, гистонового кода и метилирования ДНК.…”
unclassified